A hyperpolarization-activated inward current in heart interneurons of the medicinal leech - Angstadt, JD (J Neurosci, 1989)
Heart interneurons (HN cells) in isolated ganglia of the medicinal leech were voltage-clamped with single microelectrodes. Hyperpolarizing voltage steps elicited a slow inward current (Ih), which underlies the characteristic depolarizing response of HN cells to injection of prolonged hyperpolarizing current pulses (Arbas and Calabrese, 1987a). The conductance underlying Ih begins to activate near -mV and is fully activated between -70 and -80 mV. The activation kinetics of Ih are slow and voltage dependent. The activation time constant (tau h) ranges from approximately 2 sec at -60 mV to near 700 msec at -100 mV. Ih persists in low Ca2+ (0.1 mM), 5 mM Mn2+ saline and exhibits a reversal potential of -21 +/- 5 mV. The reversal potential is shifted by altering [Na+]o or [K+]o but is unaffected by changes in [Cl-]o. Ih is blocked by extracellular Cs+ (1–5 mM) but not Ba2+ (5 mM) or TEA (25 mM). Low concentrations of Cs+ (100–200 microM) cause a partial block that exhibits strong voltage dependence. Temperature changes were also shown to affect Ih. Both the rate of activation and the steady-state amplitude of Ih are enhanced by temperature increases. HN cells are interconnected by inhibitory chemical synapses, and their normal electrical activity consists of bursts of action potentials separated by periods of inhibition. During the inhibitory phase of rhythmic bursting activity, HN cells hyperpolarize to a voltage range where Ih is activated. Block of Ih with extracellular Cs+ (4 mM) disrupted the normal bursting activity of HN cells. These results are consistent with the hypothesis that Ih contributes to escape from inhibitory inputs during normal bursting activity.